Empathy at Work - Edith Scarletto; Chris Robinson-Nkongola (In the Library with the Lead Pipe, 2023)
In Brief: The purpose of this article is to center the experiences of librarians of color in academic libraries through a discussion of microaggressions and pandemic experiences of racial exclusion. It draws on a synthesis of the literature of microaggressions and the psychology of perspective taking.